2021
DOI: 10.2147/opth.s296345
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of COVID-19-Related Deferral of Intravitreal Injection Visits

Abstract: Purpose To determine secondary effects of the mandated COVID-19 pandemic closure period for elective treatment on non-elective, injection-based retina care and outcomes. Patients and Methods In this cross-sectional, retrospective analysis of a single-provider outpatient clinic across multiple satellites, consecutive patients returning for intravitreal injections (IVIs) of anti-vascular endothelial growth factor or corticosteroids were identified as “delayed” or “undelay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 12 publications
2
16
1
Order By: Relevance
“…While the decrease in clinical volume was not as dramatic, the number of intravitreal injections administered did not experience full recovery. At the Bascom Palmer Eye Institute in the USA during the “new normal” of operations from June 18 to August 7, 2020, a 9.9% decrease in intravitreal injections was noted compared to the corresponding period in 2019 [ 27 ]. Similarly, in France, there was a 11.5% decrease in observed intravitreal anti-VEGF injections compared to expected injections (extrapolated from the prior two years) in the period following lockdown (May 11–June 7, 2020).…”
Section: Real-world Impact On Practice Patternsmentioning
confidence: 99%
“…While the decrease in clinical volume was not as dramatic, the number of intravitreal injections administered did not experience full recovery. At the Bascom Palmer Eye Institute in the USA during the “new normal” of operations from June 18 to August 7, 2020, a 9.9% decrease in intravitreal injections was noted compared to the corresponding period in 2019 [ 27 ]. Similarly, in France, there was a 11.5% decrease in observed intravitreal anti-VEGF injections compared to expected injections (extrapolated from the prior two years) in the period following lockdown (May 11–June 7, 2020).…”
Section: Real-world Impact On Practice Patternsmentioning
confidence: 99%
“…Reports have already shown that missed injections during COVID-19 have resulted in more submacular hemorrhages, which can cause significant visual loss. 7 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…Ashkenazy et al studied the short-term effect of deferral of intravitreal injection visits due to COVID-19 pandemic. 17 They found that patients with delayed visits had a greater decline in visual acuity of 3 letters and higher rates of worsening OCT results. 17 In their study about the delay of intravitreal injection, Elfalah et al concluded that delay of more than 2 months and the previous need for 3 or more injections were significant poor prognostic factors for visual outcome for patients with DME.…”
Section: Discussionmentioning
confidence: 99%
“… 17 They found that patients with delayed visits had a greater decline in visual acuity of 3 letters and higher rates of worsening OCT results. 17 In their study about the delay of intravitreal injection, Elfalah et al concluded that delay of more than 2 months and the previous need for 3 or more injections were significant poor prognostic factors for visual outcome for patients with DME. 18 Another important issue is the negative impact of delaying the treatment of diabetic patients for their diabetes and co-morbidities.…”
Section: Discussionmentioning
confidence: 99%